The Application of Bay Leaf Decoction in Hypertension Patients (Literature Review) - Laily Hidayah, Nur; Erna Marisa, Dewi; Karlina, Nonok (INDOGENIUS, 2025)
Background & Objective: The increase in non-communicable diseases (NCDs) poses a challenge to the healthcare sector in maintaining quality of life. One of the most prevalent NCDs today is hypertension. Hypertension is classified as a silent killer and is spreading worldwide. Hypertension can be managed through pharmacological and non-pharmacological therapies. Non-pharmacological therapy can be administered through complementary therapy, such as herbal medications, and one herbal treatment believed to lower hypertension is the use of boiled bay leaf water. Method: The research method used a literature review of studies published between 2020 and 2024. The literature search employed a data strategy using the keywords “hypertension” and “bay leaves,” utilizing the Google Scholar and PubMed databases. The criteria included articles discussing the relationship between hypertension and bay leaves, with full-text availability. Result: The results from 10 articles indicate that consuming a decoction of bay leaves is effective in lowering blood pressure in hypertensive patients. Conclusion: It is recommended that hypertensive patients consume a decoction of bay leaves regularly to achieve effective results, but they should also maintain a balanced diet and engage in sufficient physical activity.